Comparative Analysis of Performance and Emission Characteristics of Compression Ignition Engine using Biodiesel and Microemulsion Based Bio Fuel Derived from Grape-seeds - Singh, Chandanpreet; Singh, Sandeep; Sarma, A. K. (Asian Journal of Engineering and Applied Technology, 2018)
Rapid declining of fossil fuel resources has generated awareness towards the development of various alternates to the conventional fuel resources. Grapes being grown worldwide, with India have the potential of making up a good feedstock. Grape-seed oil from grape-seeds was extracted with the aid of Soxhlet apparatus with a maximum yield of 18%. In Biodiesel making, the viscosity of feedstock oil was reduced in a single step transesterification process. Bio Fuel prepared by microemulsification process named as Microemulsion Based Bio Fuel (MBBF). An addition of 1% 2- Ethylhexyl nitrate was done in MBBF to study its effect in comparison to MBBF itself. In this present work, the Performance and Emission characteristics of a CI engine fuelled with 4 fuels (B20, B100, MBBF and MBBF1%) were evaluated. The performance parameters studied include Brake Thermal Efficiency, Brake Power and Brake Specific Fuel Consumption, whereas Emissions parameters include Oxides of Nitrogen, Hydrocarbons, Carbon monoxide and Carbon dioxide. The results obtained in the experiment were compared with values of Petrodiesel. Major improvements had been observed in the performance parameters of the engine as well as exhaust emissions. It was concluded that B20 fuel amongst all the Bio Fuels acted as the best alternate fuel.